Multivariate analysis of nano additives on biodiesel fuelled engine characteristics. (1st September 2020) - Murugesan, A.; Avinash, A.; Gunasekaran, E. James; Murugaganesan, A.
Graphical abstract: Highlights: Al2 O3 and CeO2 nanoparticles were separately blended with waste cooking oil biodiesel blend (B20). The optimum quantity of nanoparticles was identified by performing principal component analysis. Metal oxide based nanoparticles improved thermal efficiency (1.6%) and fuel economy (8%). The addition of nanoparticles reduced CO (5%), HC (9%), NOx (8%) and smoke (16%) emissions. Nano dispersed fuels advanced the start angle of combustion and shortened the ignition delay period. Abstract: Nanofuels are new type of fuels that use nano additives (nanoparticles) to improve the engine performance, combustion and reduce exhaust emissions. In this perspective, this research investigates the performance of direct injection compression ignition engine fuelled with waste cooking oil biodiesel blend (B20) with and without nano additive dispersion. The waste cooking oil biodiesel was produced by alkaline transesterification. The aluminum oxide and cerium oxide nanoparticles were dispersed in biodiesel blend at different weight mixtures with the aid of ultrasonic cleaner bath. In this work, six test fuels were prepared by adding different concentration of nano particles (250 mg/1 to 750 mg/l at the interval of 250). It was noted from the research work that the presence of highly reactive surface promoted the chemical reactivity which resulted in better combustion. The brake thermal efficiency and specific fuel consumption of nanoparticles dispersed biodiesel blend improved by 1.6% and 8%. In addition, the products of incomplete combustion such as carbon monoxide, unburnt hydrocarbon, and smoke density reduced appreciably up to 5%, 9%, and 16%, respectively. On the other hand, the product of complete combustion (oxides of nitrogen) reduced up to 8%. The study of combustion parameters revealed that nano dispersed fuels advanced the start angle of combustion, allows more fuel to react with oxygen and enhances rapid evaporation. Finally, the multivariate analysis of experimental data showed that the addition of 500 mg/l of aluminum oxide and 500 mg/l of cerium oxide nanoparticles in B20 blend exhibited improved engine characteristics.